2019
DOI: 10.1002/sim.8425
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of two novel transformation models

Abstract: Continuous response variables are often transformed to meet modeling assumptions, but the choice of the transformation can be challenging. Two transformation models have recently been proposed: semiparametric cumulative probability models (CPMs) and parametric most likely transformation models (MLTs). Both approaches model the cumulative distribution function and require specifying a link function, which implicitly assumes that the responses follow a known distribution after some monotonic transformation. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…We used a proportional odds logistic ordinal regression model for continuous data [i.e., a cumulative probability model with logit link (61,62)] to assess the impact of distinct regressors on multisensory spatial processing. For the CCE task, we regressed the mean difference in RT during congruent and incongruent visuo-tactile stimulation, as well as the change in accuracy, on gender, age, full-scale IQ, baseline tactile performance, and diagnostic group.…”
Section: Analyses and Statistical Modelingmentioning
confidence: 99%
“…We used a proportional odds logistic ordinal regression model for continuous data [i.e., a cumulative probability model with logit link (61,62)] to assess the impact of distinct regressors on multisensory spatial processing. For the CCE task, we regressed the mean difference in RT during congruent and incongruent visuo-tactile stimulation, as well as the change in accuracy, on gender, age, full-scale IQ, baseline tactile performance, and diagnostic group.…”
Section: Analyses and Statistical Modelingmentioning
confidence: 99%
“…, a J }. Liu et al (2017) and Tian et al (2020) have shown that CPMs can be fit to and work well for continuous and mixed types of responses. CPMs have also been shown to be consistent and asymptotically normal, with variance consistently estimated with the inverse of the information matrix under mild conditions including boundedness of the outcome variable (Li et al, 2022).…”
Section: Cumulative Probability Modelsmentioning
confidence: 99%
“…< ϑ M . It should be noted that nonparametric methods of the transformation function h dominate the literature, and smooth low-dimensional spline approaches only recently received more attention; see [14] for a comparison of the two approaches.…”
Section: B Most Likely Transformationmentioning
confidence: 99%